“I’m not the same, but I’m not sorry”: exploring dialogical positioning in the self-transformation of a former politically violent militant - Da Silva, R. (2020)
This article traces the personal and cultural voices expressed in the life-story interview of a former politically violent militant regarding her engagement with and disengagement from the armed struggle. Rather than looking at the macro and meso aspects related to politically motivated violence, we examine micro-narratives which express individual arguments, sociocultural discourses, and negotiations within and between them, These are voiced in the dynamics that take place within the self-system at times of key identity transitions (e.g., from being a committed militant to becoming a former militant). In this vein, we highlight how the embodied emotional chords of personal positions, the development of meta-positions, and the positioning and repositioning movements within the dialogical self, facilitate the emergence of new and more adaptive meanings in the personal meaning system of former militants.